Methodology of digital content creation - Serkov, Oleksandr; Kasilov, Oleg; Voronets, Vitalii; Trubchaninova, Karyna; Churyumov, Gennady (Національний технічний університет "Харківський політехнічний інститут", 2024)
The subject of the study is the individualization of the learning process in the process of assimilating information with different levels of subjective complexity. The purpose of the study is to develop a methodology for creating digital content to manage student behavior by changing the objective complexity of the learning material. The subject of the study is to develop and theoretically substantiate methods of individualized approach of students to learning professional competences by creating individual trajectories of knowledge acquisition and assimilation. Used methods: methods of analytical modelling and artificial intelligence.

Предметом дослідженняє індивідуалізація процесу навчання під час засвоєння інформації з різним рівнем її суб’єктивної складності. Мета – розробка методології створення цифрового контенту для управління поведінкою учня за допомогою зміни об’єктивної складності навчального матеріалу. Задача – розробка та теоретичне обґрунтування методів індивідуалізованого підходу студентів для навчання професійним компетенціям шляхом створення індивідуальних траєкторій вилучення та засвоєння знань. Використані методи: методи аналітичного моделювання та штучного інтелекту.
Методологія створення цифрового контенту
Keywords: individualizationof learning; personalized learning; computer system; graph-analytical structure; індивідуалізація навчання; особисто-орієнтоване навчання; комп'ютерна система; графа-аналітична структура